Uma leitura comportamental sobre o método Paulo Freire de alfabetização: convite ao diálogo entre analistas do comportamento e educadores freireanos - Bachega, Denise (Universidade Federal de São Carlos, 2014)
This study aimed to highlight interactions in the educational environment, more specifically in literacy approaching Paulo Freire s literacy method and some aspects of his theory from the perspective of Behavior Analysis. The objectives were to conduct a behavioral reading on the application of Paulo Freire s Literacy Method on the experience of Angicos - RN (1963 ) and to develop reflections on these two conceptions of education (Behavior Analysis and Freire s theory). The study consisted of a theoretical exploratory research consulting primary and secondary sources to provide a contextualization of the educational proposals concerned; a behavioral reading on Literacy Method, and; some discussions and considerations about possible contributions between educators in these two areas. From this behavioral reading one can indicate that in the Freirean method the objectives are not restricted to the reproduction of the actions of reading and writing but they stand out the relevance of these actions for the subject and for the society in which he or she is inserted. In addition, there is also the search for a construction of a non-punitive verbal community and the discussions that integrate this proposal can be understood as a teaching condition that lead to discrimination on the social contingencies in which participants take part and also the possible ways of counter control related to these contingencies. Given the objectives of the study it is possible to indicate that while one of the key concepts of Paulo Freire s proposals is that educational practices must be committed to the radical transformation of social relations, the behavioral assertion, although recognizing the importance and influence of political aspects to education, focuses on the effectiveness of teaching conditions and are less explicit about its political position compared to the Brazilian theorist s proposals. Thus, the invitation assumed by this work is to seek for new ways of making a Science increasingly committed to the transformation of the oppressive social conditions.
Keywords: Alfabetização; Análise do comportamento; Leitura Comportamental; Paulo Freire - Método educacional; Angicos (RN); Literacy; Behavior analysis; Behavioral reading; Paulo Freire literacy method; CIENCIAS HUMANAS::PSICOLOGIA